Indirect photo-electrochemical detection of carbohydrates with Pt@g-C3N4 immobilised into a polymer of intrinsic microporosity (PIM-1) and attached to a palladium hydrogen capture membrane - Yuanzhu Zhao (2020)
© 2020 The Authors An “indirect” photo-electrochemical sensor is presented for the measurement of a mixture of analytes including reducing sugars (e.g. glucose, fructose) and non-reducing sugars (e.g. sucrose, trehalose). Its innovation relies on the use of a palladium film creating a two-compartment cell to separate the electrochemical and the photocatalytic processes. In this original way, the electrochemical detection is separated from the potential complex matrix of the analyte (i.e. colloids, salts, additives, etc.). Hydrogen is generated in the photocatalytic compartment by a Pt@g-C3N4 photocatalyst embedded into a hydrogen capture material composed of a polymer of intrinsic microporosity (PIM-1). The immobilised photocatalyst is deposited onto a thin palladium membrane, which allows rapid pure hydrogen diffusion, which is then monitored by chronopotentiometry (zero current) response in the electrochemical compartment. The concept is demonstrated herein for the analysis of sugar content in commercial soft drinks. There is no requirement for the analyte to be conducting with electrolyte or buffered. In this way, samples (biological or not) can be simply monitored by their exposition to blue LED light, opening the door to additional energy conversion and waste-to-energy applications.